2004
DOI: 10.1364/opex.12.006002
|View full text |Cite
|
Sign up to set email alerts
|

Optical second harmonic generation properties of BiB3O6

Abstract: We present studies of the optical properties of the new nonlinear material BiB3O6 for second harmonic generation from the visible to infrared. We have determined the phase-matching conditions and effective nonlinear coefficients in the three principal optical planes, acceptance bandwidths, spatial and temporal walkoff, group velocity dispersion and double phase-matching behaviour. We also report on experimental studies in this material, where efficient, high-average-power second harmonic generation of femtosec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
69
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 116 publications
(71 citation statements)
references
References 9 publications
2
69
0
Order By: Relevance
“…In fact, this corresponds to the tradition established in the nonlinear optics of monoclinic crystals [69]. Indeed, it was not before the nonlinear coefficients were transformed into this orthogonal dielectric xyz frame [70] that BIBO attracted the interest of several groups working in the field of nonlinear frequency conversion. For point group 2 symmetry, one of the principal optical axes (the x-axis in BIBO [1]) coincides with the 2-fold symmetry axis b, but the position of the other two axes depends both on wavelength and temperature (the xyz frame rotates about the b-axis).…”
Section: Bibo: Relevant Propertiesmentioning
confidence: 69%
See 1 more Smart Citation
“…In fact, this corresponds to the tradition established in the nonlinear optics of monoclinic crystals [69]. Indeed, it was not before the nonlinear coefficients were transformed into this orthogonal dielectric xyz frame [70] that BIBO attracted the interest of several groups working in the field of nonlinear frequency conversion. For point group 2 symmetry, one of the principal optical axes (the x-axis in BIBO [1]) coincides with the 2-fold symmetry axis b, but the position of the other two axes depends both on wavelength and temperature (the xyz frame rotates about the b-axis).…”
Section: Bibo: Relevant Propertiesmentioning
confidence: 69%
“…1, which corresponds to a wavelength of 810 nm [70]. The results summarized in Table 1 of [70] indicate that the deviation from the Kleinman conjecture [67] does not exceed ±10%, which equals the experimental error [68]. Thus, it is justified to assume that Kleinman symmetry holds and average the corresponding d il values.…”
Section: Bibo: Relevant Propertiesmentioning
confidence: 89%
“…Borate compounds (crystals and glasses), un-doped and doped with transition and rare-earth elements are very promising for quantum electronics and non-linear optics [1,2] scintillators and tissue-equivalent materials for thermoluminescent (TL) dosimetry [3][4][5], as well as γ and neutron detectors [6][7][8]. This also concerns lithium tetraborate crystals which are characterized by extremely high radiation stability [9,10], high transparency in a wide spectral range from VUV to far IR [11] and good TL properties [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Glass ceramics contain generally a higher mechanical and chemical stability [15,16]. Especially, borate glassceramics are attractive due to their vast commercial applications in scintillators and tissue-equivalent materials for thermoluminescence (TL) dosimeters, γ and neutron detectors [17][18][19], and nonlinear optical ceramic properties [20,21]. Changmin et al reported various optical properties of Sm 3 þ in fluoroborate ceramic [22].…”
Section: Introductionmentioning
confidence: 99%
“…Powder X-ray diffraction (XRD) measurements were carried out using Cu, K α radiation from a RINT/DMAX 2200H/PC (Rigaku, Japan) machine having a scan speed 21 for GC8, GC10, GC15, GC20, and GC24 samples, respectively, which is higher than the as-prepared glass 2.36 g/cm 3 . Refractive indices were determined by Brewster's angle method using red (632.9 nm) He:Ne lasers which were interference free from Sm 3 þ ion absorption peaks.…”
Section: Introductionmentioning
confidence: 99%